"It's more than just a game": NCCAA Division II student-athletes' perceptions of coach caring. Issue 4 (August 2020) - Schools, Jordan A; Fisher, Leslee A; Moore, Matthew J; Morris, Sierra V; Egli, Trevor J; Knust, Susannah K
The construct of care within the coach–athlete relationship has only recently been examined. However, this research has yet to include athletes' perceptions of caring coaching practice. Thus, the primary purpose of the current study was to examine self-described Christian student-athletes' perceptions of coach caring practices. Therefore, the guiding research questions were: (a) in what ways do student-athletes feel that their coaches demonstrate care? (b) In what ways have student-athletes' religion/spirituality shaped the way they understand and perceive care? (c) Does proximity to a caring coach practice—that is, those who are still competing versus those who have graduated—influence the ways in which student-athletes view coach caring? Eleven current and former student-athletes (mean age = 26 years; seven males, four females) from four different sports (basketball, cross country, soccer, and tennis) at one NCCAA school were interviewed. Data analysis was conducted by a six-person research team using Consensual Qualitative Research. Five domains were constructed to represent Christian University 1 student-athlete perceptions of: (I) how they learned coach caring, (II) how they defined a lack of coach caring, (III) how they defined coach caring, (IV) how they perceived the expression of the caring climate, and (V) how they perceived the expression of the Christian caring climate.